Analytical tuning of regulators in a cascade automatic discharge control system - D. A. Kovalev; V. A. Sharyakov; O. L. Sharyakova; V. A. Lebedeva (Современная наука и инновации, 2023)
When synthesizing automatic control systems, there is a problem with complex definition of controller parameters, and the main criterion becomes the achievement of stable operation, and the quality of the transient becomes of secondary importance. Such problems may arise in the presence of two or more nested loops in the initial system. The correct synthesis of such systems is possible by using a slave control structure that allows us to replace the inner loop with an equivalent aperiodic link of the first order. By the example of an automatic temperature control system for superheated steam, the principle of building a slave control structure and the synthesis of such a system are shown in the paper.